Volatile organic compounds (VOCs) release from different type of wastes and potential health risk to waste collectors/ Siti Rohana Mohd Yatim, Famira Othman and Muhammad Afiq Zaki - Mohd Yatim, Siti Rohana; Othman, Famira; Zaki, Muhammad Afiq (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Among air pollutants, emission of VOCs will lead to various short-term and long-term diseases based on their concentration level in the air. In this study, waste samples were prepared by collecting 15kg for each type of waste (food waste and mixed waste) and were stored in modified waste storage bins. The experiment was conducted by mimicking outdoor environmental setting for 21 days to stimulate the decomposition of the waste during extended storage period. The type of VOCs tested in this study are benzene, toluene, ethylbenzene, m-xylene, limonene and dimethyl disulphide. It was found that type of waste influenced the level of VOCs emitted with, p-value <0.05. Meanwhile, the time for waste collection does not influence the level of VOC emitted from the modified waste storage bin. Health risk assessment was also determined by calculating the Hazard Quotient, Hazard Index and Cancer Risk. For non-carcinogenic effects in this study have higher values of hazard index (HI > 1) for food waste and mixed waste which signify the occurrence of non-carcinogenic effects while the carcinogenic risk which is benzene in this study was found below the acceptable range. As a result, the determination of VOCs in a waste disposal bin and conducting health risk assessment is necessary to assess the impact on collection workers health as well as to the environment.